8.6k views
1 vote
Find the value of questions​

Find the value of questions​-example-1
User Fredashay
by
5.1k points

1 Answer

2 votes

Answer:

The simplified expression is:


(3^9y)/(2* \:81)=(243y)/(2)

Explanation:

Given the expression


(3^9* \:y)/(2* 81)

solving the expression


(3^9* \:y)/(2* 81)=(3^9y)/(162)


=(3^9y)/(3^4* \:2)
162=3^4* \:2


=(3^5y)/(2)
\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)=x^(a-b)


=(243y)/(2)
3^5=243

Therefore, the simplified expression is:


(3^9y)/(2* \:81)=(243y)/(2)

User DrowZ
by
4.7k points